2014
DOI: 10.1002/hed.23610
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of functional outcomes and quality of life between transoral surgery and definitive chemoradiotherapy for oropharyngeal cancer

Abstract: Similar quality of life was observed among patients treated by transoral surgery or chemoradiotherapy. Although the rates of subjective swallowing dysfunction were higher among the latter, confounding biases must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 20 publications
2
100
2
1
Order By: Relevance
“…Notably, 74% of patients treated with primary transoral surgery reported swallowing “as well as ever” at 1-year compared with only 32% of patients in the chemoradiation group. 35 Findings from both of these case-control studies favor better long-term swallowing recovery with upfront transoral surgery (robotic or laser) and adjuvant radiation at postoperative doses. Nevertheless, retrospective and historical comparisons do not adequately account for confounding factors that influence functional outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, 74% of patients treated with primary transoral surgery reported swallowing “as well as ever” at 1-year compared with only 32% of patients in the chemoradiation group. 35 Findings from both of these case-control studies favor better long-term swallowing recovery with upfront transoral surgery (robotic or laser) and adjuvant radiation at postoperative doses. Nevertheless, retrospective and historical comparisons do not adequately account for confounding factors that influence functional outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Some patients may experience changes in how they taste food or lose their sense of taste altogether. Still others may experience hoarseness or other voice changes that may be permanent [22]. Patients who undergo chemotherapy may experience side effects such as mucositis (severe mouth ulcers), hearing loss, nausea and vomiting, diarrhea, weakness, and fatigue [23].…”
Section: How Common Is Hpv Positive Head and Neck Cancer?mentioning
confidence: 99%
“…1113 Studies 13,14 have compared unmatched patients with OPSCC undergoing TORS and nonsurgical therapy with results suggesting better swallowing-related outcomes in patients undergoing TORS. A study examining QOL among patients with OPSCC matched on 10 factors (including age, sex, tumor stage, and tumor human papillomavirus [HPV] status) showed that patients who had undergone transoral surgery, such as TORS, had significantly higher scores in the swallowing domain at 1 year after treatment in univariable analysis (multivariable models were not generated in the study).…”
mentioning
confidence: 99%
“…A study examining QOL among patients with OPSCC matched on 10 factors (including age, sex, tumor stage, and tumor human papillomavirus [HPV] status) showed that patients who had undergone transoral surgery, such as TORS, had significantly higher scores in the swallowing domain at 1 year after treatment in univariable analysis (multivariable models were not generated in the study). 11 …”
mentioning
confidence: 99%